An NIR-Triggered Au Nanocage Used for Photo-Thermo Therapy of Chronic Wound in Diabetic Rats Through Bacterial Membrane Destruction and Skin Cell Mitochondrial Protection - Ding, Jiaxin; Gao, Binbin; Chen, Zhenhua; Mei, Xifan (Frontiers in Pharmacology, 2021)
Bacterial infection and its severe oxidative stress reaction will cause damage to skin cell mitochondria, resulting in long-lasting wound healing and great pain to patients. Thus, delayed wound healing in diabetic patients with Staphylococcus aureus infection is a principal challenge worldwide. Therefore, novel biomaterials with multifunction of bacterial membrane destruction and skin cell mitochondrial protection are urgently needed to be developed to address this challenge. In this work, novel gold cage (AuNCs) modified with epigallocatechin gallate (EGCG) were prepared to treat delayed diabetic wounds. The results showed that Au-EGCG had a high and stable photothermal conversion efficiency under near-infrared irradiation, and the scavenging rate of Au-EGCG for S. aureus could reach 95%. The production of large amounts of reactive oxygen species (ROS) leads to the disruption of bacterial membranes, inducing bacterial lysis and apoptosis. Meanwhile, Au-EGCG fused into hydrogel (Au-EGCG@H) promoted the migration and proliferation of human umbilical cord endothelial cells, reduced cellular mitochondrial damage and oxidative stress in the presence of infection, and significantly increased the basic fibroblast growth factor expression and vascular endothelial growth factor. In addition, animal studies showed that wound closure was 97.2% after 12 days of treatment, and the healing of chronic diabetic wounds was significantly accelerated. Au-EGCG nanoplatforms were successfully prepared to promote cell migration and angiogenesis in diabetic rats while removing S. aureus, reducing oxidative stress in cells, and restoring impaired mitochondrial function. Au-EGCG provides an effective, biocompatible, and multifunctional therapeutic strategy for chronic diabetic wounds.